Haematological changes after switching from stavudine to zidovudine in HIV-infected children receiving highly active antiretroviral therapy - L. Aurpibul (2018)
Objective: In resource-limited countries, stavudine (d4T) is commonly used as part of the initial highly active antiretroviral therapy (HAART) regimen. Many patients who subsequently develop lipodystrophy switch from d4T to zidovudine (ZDV), a drug that can be myelotoxic. We aimed to study the spectrum and severity of haematological changes following this substitution. Methods: This was a retrospective cohort study. The inclusion criteria were as follows: HIV-infected children were included who (1) were 2-15 years old at the time of HAART initiation, (2) had not been diagnosed as having haematological diseases, (3) had been receiving a first HAART regimen consisting of either nevirapine or efavirenz, together with lamivudine and d4T, for at least 48 weeks and (4) had switched from d4T to ZDV at least 48 weeks previously. Results: Seventy-eight children were included in the study. Thirty-six (46%) were male. The mean age was 10.3 years (standard deviation 3.1 years). The switch had been made a median time of 65 weeks (range 48-97 weeks) previously. There was no significant change in CD4 lymphocyte count or percentage, or HIV RNA level, after the switch. There was a statistically significant decrease in haemoglobin level (12.6 vs. 12.1 g/dL; P < 0.001), total white blood cell (WBC) count (8088 vs. 6910 cells/μL; P < 0.001) and absolute neutrophil count (ANC) (4320 vs. 3448 cells/μL; P < 0.001). However, the decreases never reached Division of AIDS grade 3 or 4 severity, and none of the patients had clinical symptoms or signs of anaemia, leukopenia, or neutropenia. No participant had to discontinue ZDV during the 48-week follow-up period. Conclusion: In a paediatric population, statistically significant decreases in haemoglobin level, WBC count and ANC occurred following the substitution of d4T with ZDV, but the magnitudes of the decreases were small and not clinically significant. © 2008 British HIV Association.